Calibration of CEP dependent electron spectra - Hoff, Dominik; Sayler, A. Max; Krüger, Michael; Maisenbacher, Lothar; Paulus, Gerhard G.; Hommelhoff, Peter (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Here we present a technique to determine the absolute carrier-envelope phase (CEP) dependence of electron rescattering in strong-field ionization. First, this requires a detailed knowledge of the spatial dependence of the CEP in the focus of few-cycle laser pulses. Second, one needs a well known reference to calibrate the process to the CEP. In our case we use ab-initio 3D-TDSE simulations of above-threshold ionization (ATI) of atomic Hydrogen to calibrate experimental electron spectra of H, these can then be used to calibrate ATI-spectra of Xenon. The latter can serve as a reference for the electron rescattering at noble gases and nanostructures. With this calibration it is possible to unravel different contributions that are responsible for a phase shift between atomic gases and nanostructures.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Above-threshold ionization; Attosecond-science; CEP; Light-wave electronics; Nano optics